IMPLEMENTASI KEGIATAN GOTONG ROYONG DALAM MEMBINA SIKAP MANDIRI ANAK DI KELOMPOK B RA MUSTHAFAWIYAH - Dirga Ayunda Putri; Mavianti Mavianti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to determine the Implementation of Mutual Cooperation Activities in Fostering Children's Independent Attitudes in Group B RA Musthafawiyah. This study uses a qualitative description approach, aiming to describe how the implementation of mutual cooperation activities in fostering the independent attitude of class B RA Musthafawiyah children. The subjects of this study were RA Musthafawiyah and the objects of this study were the principal, teachers and also students of class B RA musthafawiyah. Based on the results of this study, children's independence has been instilled from an early age so that the results obtained are also quite good, children are used to being independent and disciplined in carrying out their activities at school. In addition, children's tolerance has also begun to grow and develop well, judging from the simple things they do with their classmates. The fruit of the teacher's patient and gentle attitude when applying good habits to children. There are not many children who have less developed independence, this happens because of a lack of parental cooperation in maximizing the development of independence that is applied at school.